The rôles of plankton and neuston microbial organic matter in climate regulation. (12th October 2021) - Jenkinson, Ian R; Berdalet, Elisa; Chin, Wei-Chun; Denis, Michel; Ding, Haibing; Duan, Jizhou; Elias, Florence; Emri, Igor; Karn, Santosh K; Li, Zhuo; Malej, Alenka; Mari, Xavier; et al.
Abstract: Plankton and neuston microbes produce organic matter (OM), which accumulates in the sea surface microlayer (SML). Fluxes of heat and momentum exchange across the sea-air interface, as do fluxes of matter, including greenhouse gases, aerosols, microbes (algae, bacteria sensu lato and viruses) and other substances. At least at calm to moderate windspeeds, microbial OM (MOM) in the SML reduces these fluxes. Another MOM fraction, foam, covers a part of the ocean surface. Ocean foam increases mean ocean albedo because it reflects solar radiation, thus cooling the ocean and the Earth. The rheological properties of MOM and the reduction of sea-air fluxes depend on microbial abundance and taxonomic composition, as do the formation and persistence of foam. Genomic regulation of MOM secretion may thus be helping to regulate air-sea fluxes and climate. Unpredictable changes in abundance and taxonomic composition of these microbial communities may be adding uncertainty to global and more local climate. Some of this uncertainty could be mitigated by studying the ecology and genomics of the surface microbial community together with chemical and rheological properties of their secreted MOM and its effects on sea-air fluxes and foam coverage, to incorporate into climate models.